Pengembangan Tes Diagnostik Four-Tier Multiple Choice Pendeteksi Pemahaman Konsep Materi Sistem Koordinasi - Riandy Pratama (Journal on Education, 2023)
A diagnostic test with a four tier design to detect students' understanding of concepts. The advantage of the Four Tier choice diagnostic test is that through the four level diagnostic test the teacher can distinguish the level of confidence in the answers and the level of confidence in the reasons chosen by students so that they can dig deeper into the strength of students' understanding of concepts. Diagnostic tests are carried out on students who have received coordination system material. This research is a research and development (R&D) study with the 4D method, namely define, design develop and disseminate. The subjects of this study were XII IPA 3, 4 and 5 students of SMAN 1 Terbanggi Besar. The results of the coordination system material diagnostic test showed good and valid with a CVR value of 0.80 and a CVI score consisting of 35 questions with 8 validators of 0.78 with the appropriate category and reliability of 0.916 so that the instrument was reliable. Research at SMAN 1 Terbanggi Besar in high class 46.47%, medium 38.81 and low 45.86%. It can be concluded that students who understand the concept of coordination system material on the nervous system and hormones with indicators are identifying the structure of human nerve cells with sub-concepts Cell structure and function human nerves, with indicators of the working mechanism of the entry of light into the eye. The eye is an organ that functions to receive information in visual form, thus there are still many students who do not understand many other concepts in the material of the human coordination system.